A comparison between partially peeled hulless barley and whole grain hulless barley: beneficial effects on the regulation of serum glucose and the gut microbiota in high-fat diet-induced obese mice. Issue 2 (20th December 2022) - Meng, Yantong; Meng, Qingjia; Li, Chang; Wang, Mengqian; Li, Siqi; Ying, Jian; Zheng, Hao; Bai, Shuqun; Xue, Yong; Shen, Qun
Abstract : Hulless barley can improve glucose metabolism, reduce fat accumulation and repair gut microbiota structure. And there was little loss of beneficial effects when hulless barley was moderately peeled. Abstract : Though the hypoglycemic effect of whole grain hulless barley ( Hordeum vulgare L.) has been documented, whether glucose metabolism would be improved by hulless barley with moderate peeling is still unclear. The purpose of this study was to compare the differences in glucose metabolism and gut microbiota between partially (10%) peeled hulless barley (PHB) and whole grain hulless barley (WHB) intervention in obese mice induced by a high-fat diet. The results showed that both PHB and WHB interventions significantly improved the impaired glucose tolerance, fat accumulation in fat and liver tissues, and the impaired intestinal barrier in mice. The dysbiosis of gut microbiota was improved and the relative abundance of some beneficial bacteria such as genera Lactobacillus, Bifidobacterium, Ileibacterium, and norank_f__Mutibaculaceae was increased by both, PHB and WHB, interventions. Spearman correlation analysis revealed that the abundance of Bifidobacterium was negatively correlated with the area under the blood glucose curve. In conclusion, our results provide evidence that hulless barley improved the gut microbiota and impaired glucose tolerance in mice, and also showed that there was little loss of hypoglycemic effect even when hulless barley was moderately peeled.